Prognostic value of serum uric acid in patients with acute heart failure: A meta-analysis. Issue 8 (February 2019) - Huang, Gang; Qin, Juan; Deng, Xuejun; Luo, Guiquan; Yu, Dongmei; Zhang, Mei; Zhou, Shiheng; Wang, Lei
Abstract: Background: Conflicting results have been reported on the prognostic significance of serum uric acid (SUA) in patients with acute heart failure (AHF). This meta-analysis aimed to determine the prognostic significance of SUA level in patients with AHF. Methods: We made a comprehensive literature search in Pubmed and Embase databases from inception to April 6, 2018. All available observational studies or post hoc analysis of randomized controlled trial that evaluated the prognostic value of SUA level in patients with AHF were eligible. Outcome of interests were all-cause mortality and the combined endpoint of death or readmission. Prognostic values of SUA level were summarized as higher vs lower SUA category or per 1 mg/ml SUA rise. Results: Ten studies involving 12, 854 AHF patients were identified and analyzed. AHF patients with the highest SUA level had an increased risk of all-cause mortality (risk ratio [RR] 1.43; 95% confidence intervals [CI] 1.31–1.56) and combined endpoint of death or readmission (RR 1.68; 95% CI 1.33–2.13) after adjusting potential variables. In addition, per 1 mg/ml SUA rise significantly increased by 11% and 12% higher risk all-cause mortality and combined endpoint of death or readmission, respectively. A leave out 1 study sensitivity analysis confirmed the reliability of the pooling effect sizes. Conclusion: This meta-analysis indicates that elevated SUA level independently predicts all-cause mortality and the combined endpoint of death or readmission in AHF patients. Measurement of SUA level may improve risk stratification of adverse outcomes in these patients.